2018
DOI: 10.1002/adts.201800105
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling and Simulation of Nano‐Carriers Delivery through Biological Barriers—A Review

Abstract: The past several decades have witnessed the explosion of nanomedicine for cancer therapy, where notable research efforts have been made in synthesizing and delivering nano-carriers (NCs) to specific tumor sites. The effective treatment of cancer with nanomedicine poses the requirements of high solubility, prolonged circulation, low toxicity, strong targeting ability, specific distribution, and high tissue penetration capability of NCs, involving interdisciplinary research and posing challenges to the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 335 publications
(405 reference statements)
0
22
0
Order By: Relevance
“…This suggested that cellular uptake of 3 and 5 was an energy-dependent process and was closely related to the energy provided by aerobic glycolysis metabolism in cancer cells. Considering the energy-dependent pathway of cellular uptake by NPs (Mayor and Pagano, 2007, Shi and Tian, 2019), cells were pre-treated with chlorpromazine (CPZ, clathrin-dependent endocytosis inhibitor), amiloride (AMR, micropinocytosis inhibitor), and methyl-β-cyclodextrin (MβCD, caveolin-dependent endocytosis inhibitor), and then incubated with 3 or 5 . We found that HeLa and MCF-7 cells showed different cell uptake inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that cellular uptake of 3 and 5 was an energy-dependent process and was closely related to the energy provided by aerobic glycolysis metabolism in cancer cells. Considering the energy-dependent pathway of cellular uptake by NPs (Mayor and Pagano, 2007, Shi and Tian, 2019), cells were pre-treated with chlorpromazine (CPZ, clathrin-dependent endocytosis inhibitor), amiloride (AMR, micropinocytosis inhibitor), and methyl-β-cyclodextrin (MβCD, caveolin-dependent endocytosis inhibitor), and then incubated with 3 or 5 . We found that HeLa and MCF-7 cells showed different cell uptake inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Our DRL algorithm is model‐free so that it can be used to realize continuous control on micro/nano motors with other dynamic models [ 1,22,43–47 ] (e.g., other actuation mechanisms, hydrodynamics, etc.) beyond what has been considered here.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nanoparticle-based drug delivery, which integrates emerging nanotechnologies with traditional chemotherapeutic drugs to get rid of drawbacks in traditional therapies as well as offer new possibilities to optimize cancer treatment, has always been one of the focuses in the eld of nanomedicine. [8][9][10] In general, the key advantages of nanodrug delivery are longer circulating halflives, improved pharmacokinetics, selective intratumoral accumulation, and lower systemic toxicity. Meanwhile, some other emerging minimally invasive therapies, such as photothermal Qun Guan is currently a PhD student.…”
Section: Introductionmentioning
confidence: 99%